2013
DOI: 10.1371/journal.pone.0053899
|View full text |Cite
|
Sign up to set email alerts
|

Microplate-Test for the Rapid Determination of Bacteriophage-Susceptibility of Campylobacter Isolates—Development and Validation

Abstract: A simple susceptibility test using 800 isolates of one Campylobacter strain with different degrees of susceptibility and four bacteriophages of the British phage typing scheme was developed and examined for its suitability. The test presented is economically cheaper and less time consuming than the conventional agar overlay plate assay and therefore enables the monitoring of changes in the susceptibility pattern during phage therapy under practical field conditions. The main objective of this study was to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
1
13
0
2
Order By: Relevance
“…Experiments that showed significant reductions in Campylobacter numbers in the cecal contents of experimental birds were first reported in 2005(Loc Carrillo et al 2005Wagenaar et al 2005). Further studies were carried out that confirmed the promising potential of this application (El-Shibiny et al 2007Carvalho et al 2010;Fischer et al 2013). Bacteriophages successfully diminished the numbers of C. jejuni in cooked and raw beef by 2 log 10 (Bigwood et al 2008) as well as on poultry meat surfaces (Atterbury et al 2003;Goode et al 2003).…”
Section: Examples Of Applications Of Bacteriophage As a Biocontrol Agmentioning
confidence: 85%
“…Experiments that showed significant reductions in Campylobacter numbers in the cecal contents of experimental birds were first reported in 2005(Loc Carrillo et al 2005Wagenaar et al 2005). Further studies were carried out that confirmed the promising potential of this application (El-Shibiny et al 2007Carvalho et al 2010;Fischer et al 2013). Bacteriophages successfully diminished the numbers of C. jejuni in cooked and raw beef by 2 log 10 (Bigwood et al 2008) as well as on poultry meat surfaces (Atterbury et al 2003;Goode et al 2003).…”
Section: Examples Of Applications Of Bacteriophage As a Biocontrol Agmentioning
confidence: 85%
“…Phages were propagated on their C. jejuni host strains NCTC 12661, 12664, and 12660 as described elsewhere (29), 100 l each of the phage suspension and host Campylobacter being added to 5 ml of liquefied NZCYM agar (Carl Roth GmbH & Co KG, Germany; 0.7% agar-agar; Merck). The agar was poured onto NZCYM plates containing 1.5% agaragar.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, broad-spectrum phage cocktails in sufficient doses for passive reduction of different host strains are needed. For large-scale practice, additional research is required, particularly regarding guaranteeing the absence of virulence genes and monitoring occurring resistances against phages (29).…”
Section: Reduction Of Campylobactermentioning
confidence: 99%
“…Se estima que puede llegar a afectar por encima de 2.4 millones de personas por año en EEUU (CDC 2014). La mayor parte de las ETA, causadas por este agente, son transmitidas por carne de aves contaminadas (Fischer et al 2013); aunque se ha determinado también en la leche cruda y agua contaminada como fuentes de infección (Indikova et al 2015).…”
Section: Introductionunclassified
“…Se estima que puede llegar a afectar por encima de 2.4 millones de personas por año en EEUU (CDC 2014). La mayor parte de las ETA, causadas por este agente, son transmitidas por carne de aves contaminadas (Fischer et al 2013); aunque se ha determinado también en la leche cruda y agua contaminada como fuentes de infección (Indikova et al 2015).Costa Rica presenta un consumo per cápita anual de 23.42 kg de productos y subproductos de la cadena de carne avícola (Wright 2010). Un alto consumo de carne de ave, sin el debido tratamiento en la producción, venta o preparación para consumo, implica un mayor riesgo de infección.…”
unclassified